2013
DOI: 10.5897/ajpp12.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic properties of Curcuma longa and Tagetes erecta on cancer cell line (Hep2)

Abstract: Cancer is the major public difficulty and one of the top causes of death in prosperous countries. Conventional plants are precious source of novel cytotoxic agents and play a critical role in health concern. Due to its wide range of biological and pharmacological effects and lack of toxicity, curcumin and lutein were selected for this study. Curcumin and lutein were isolated from rhizomes of Curcuma longa and petals of Tagetes erecta. The isolated pigments were quantified spectroscopically and separated by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…A much lower amount of viable cells (less than 10%) were detected at this range of concentrations, which showed the maximum inhibition concentration. These results were in accordance with previous studies performed on T. erecta conducted by Gupta and Gupta [6], Vallisuta and Nukoolkarn [25], and Ayyadurai and Valarmathy [26]. Interestingly, the study conducted by [7] for determining the cytotoxic activity of the essential oils of four plants (T. erecta L., Tetradenia riparia, Bidens sulphurea, and Foeniculum vulgare) against six tumor cell lines murine melanoma (B16F10), human colon carcinoma (HT29), human breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), human hepatocellular liver carcinoma (HepG2), and human glioblastoma (MO59J, U343, and U251), showed that cancer cells have higher sensitivity to the oil of T. erecta.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…A much lower amount of viable cells (less than 10%) were detected at this range of concentrations, which showed the maximum inhibition concentration. These results were in accordance with previous studies performed on T. erecta conducted by Gupta and Gupta [6], Vallisuta and Nukoolkarn [25], and Ayyadurai and Valarmathy [26]. Interestingly, the study conducted by [7] for determining the cytotoxic activity of the essential oils of four plants (T. erecta L., Tetradenia riparia, Bidens sulphurea, and Foeniculum vulgare) against six tumor cell lines murine melanoma (B16F10), human colon carcinoma (HT29), human breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), human hepatocellular liver carcinoma (HepG2), and human glioblastoma (MO59J, U343, and U251), showed that cancer cells have higher sensitivity to the oil of T. erecta.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…The study of cytotoxic properties of turmeric on liver cancer cells (Hep-2) showed that the cytotoxicity mediated by curcumin in a dose-dependent manner leads to apoptosis of cancer cells through mitochondrial pathway. 83 …”
Section: Resultsmentioning
confidence: 99%
“…C. longa is used by traditional healers in To Manui ethnic to treat various symptoms/diseases such as diabetes, pre, and post-natal care and flu/colds. Curcumin contained in C. longa and most species of the Zingiberaceae family are the main components responsible for various pharmacological effects including antidiabetic, anticancer, antiinflammatory, antimicrobial, antifungal, anti-HIV and as hepato-and nephroprotector (Kurapati and Samikkannu 2012;Ayyadurai et al 2013;Rafieian-Kopaei et al 2014;Hamidpour et al n.d.;Schmidt et al 2015;Shukla et al 2016). Olatunde et al (2014) reported oral administration of water extract C. longa 200 mg/kg bw for 28 days had an antihyperglycemic effect in diabetic rats induced by alloxan.…”
Section: Discussionmentioning
confidence: 99%